2010
DOI: 10.1002/adma.201000369
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Hyperbranched Polymers and Its Biomedical Applications

Abstract: Hyperbranched polymers (HBPs) are highly branched macromolecules with a three-dimensional dendritic architecture. Due to their unique topological structure and interesting physical/chemical properties, HBPs have attracted wide attention from both academia and industry. In this paper, the recent developments in HBP self-assembly and their biomedical applications have been comprehensively reviewed. Many delicate supramolecular structures from zero-dimension (0D) to three-dimension (3D), such as micelles, fibers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
337
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(341 citation statements)
references
References 207 publications
1
337
0
3
Order By: Relevance
“…As previous trials with grafting to approaches led to low functionalization of the hyperbranched template, and removal of unreacted amphiphilic double-shell building blocks turned out to be quite tedious, we decided to use the grafting-from approach. As already discussed in other publications, multiple hydroxyl groups on one branched scaffold allow the polymerization to simultaneously take place at ideally all accessible hydroxyl groups [23,24]. This concept of a so-called macroinitiator was used in our herein-presented work to polymerize ε-caprolactone in a tin-catalyzed ring opening polymerization.…”
Section: ε-Caprolactone Polymerization Using Hpes-oh 2 In Grafting Frommentioning
confidence: 90%
“…As previous trials with grafting to approaches led to low functionalization of the hyperbranched template, and removal of unreacted amphiphilic double-shell building blocks turned out to be quite tedious, we decided to use the grafting-from approach. As already discussed in other publications, multiple hydroxyl groups on one branched scaffold allow the polymerization to simultaneously take place at ideally all accessible hydroxyl groups [23,24]. This concept of a so-called macroinitiator was used in our herein-presented work to polymerize ε-caprolactone in a tin-catalyzed ring opening polymerization.…”
Section: ε-Caprolactone Polymerization Using Hpes-oh 2 In Grafting Frommentioning
confidence: 90%
“…This is an unexpected and interesting result as it is in contrast to the view of HBP as unimolecular entities. The number of morphologies and structures of assemble HBPs and their unique properties have converted them in promising systems for biomedical applications [15][16][17]. Self-assembling HBPs are formed by hydrophobic (hydrophilic) dendritic core and hydrophilic (hydrophobic) arms.…”
Section: Introductionmentioning
confidence: 99%
“…General strategies for the synthesis of MSPs have been covered in several excellent reviews. 18,[151][152][153] The potential applications of the hyperbranched aliphatic polyethers and their corresponding MSPs, for example, as unimolecular containers, for molecular self-assembly and biomedical purposes have been covered in other reviews [154][155][156] and will be discussed with a special focus on hyperbranched aliphatic polyethers in different sections of this highlight article.…”
Section: Multiarm Star Copolymers With a Hyperbranched Corementioning
confidence: 99%
“…Yan and coworkers extensively studied MSPs based on PEHO with a certain focus on self-assembly and biomedical applications. 155 Especially, PEHOs with PEG arms show unique self-assembly behavior up to the formation of macroscopic visible fibers in acetone (see section ''Solution Properties''). 107,108,178 In ongoing studies, it was found that the DB of PEHO has a significant effect on the aggregation behavior, as the MSPs can self-assemble into vesicles, wormlike micelles, and spherical micelles with a decrease in DB of the hyperbranched core, respectively.…”
Section: Multiarm Star Copolymers With a Hyperbranched Corementioning
confidence: 99%